Cardiac rehabilitation via telerehabilitation in COVID-19 pandemic situation - Dian M. Sari (The Egyptian Heart Journal, 2021)
Abstract Background Adherence to medication and lifestyle changes are very important in the secondary prevention of cardiovascular disease. One of the ways is by doing a cardiac rehabilitation program. Main body of the abstract Cardiac rehabilitation program is divided into three phases. The cardiac rehabilitation program’s implementation, especially the second phase, center-based cardiac rehabilitation (CBCR), has many barriers not to participate optimally. Therefore, the third phase, known as home-based cardiac rehabilitation (HBCR), can become a substitute or addition to CBCR. On the other hand, this phase is also an essential part of the patients’ functional capacity. During the coronavirus disease-2019 pandemic, HBCR has become the leading solution in the cardiac rehabilitation program’s sustainability. Innovation is needed in its implementation, such as telerehabilitation. So, the cardiac rehabilitation program can be implemented by patients and monitored by health care providers continuously. Short conclusion Physicians play an essential role in motivating patients and encouraging their family members to commit to a sustainable CR program with telerehabilitation to facilitate its implementation.